Defibrotide modulates pulmonary endothelial cell activation and protects against lung inflammation in pre-clinical models of LPS-induced lung injury and idiopathic pneumonia syndrome - Klein, Orly R.; Ktena, Yiouli P.; Pierce, Elizabeth; Fu, Han-Hsuan; Haile, Azeb; Liu, Chen; Cooke, Kenneth R. (Frontiers in Immunology, 2023)
Introduction: A multiple organ dysfunction syndrome (MODS) workshop convened by the National Institute of Child Health and Human Development in 2015 identified acute respiratory distress syndrome (ARDS) and complications of allogeneic blood and marrow transplantation (allo-BMT) as contributors to MODS in pediatric patients. Pulmonary dysfunction also remains a significant complication of allo-BMT. Idiopathic pneumonia syndrome (IPS) defines non-infectious, acute, lung injury that occurs post-transplant. Injury and activation to endothelial cells (ECs) contribute to each form of lung inflammation. Methods: Two murine models were employed. In an ARDS model, naïve B6 mice receive an intravenous (i.v.) injection of lipopolysaccharide (LPS). In the established model of IPS, naïve B6D2F1 mice receive lethal total body irradiation followed by BMT from either allogeneic (B6) or syngeneic (B6D2F1) donors. Lung inflammation was subsequently assessed in each scenario. Results: Intravenous injection of LPS to B6 mice resulted in enhanced mRNA expression of TNFα, IL-6, Ang-2, E-, and P-selectin in whole lung homogenates. The expression of Ang-2 in this context is regulated in part by TNFα. Additionally, EC activation was associated with increased total protein and cellularity in broncho-alveolar lavage fluid (BALF). Similar findings were noted during the development of experimental IPS. We hypothesized that interventions maintaining EC integrity would reduce the severity of ARDS and IPS. Defibrotide (DF) is FDA approved for the treatment of BMT patients with sinusoidal obstruction syndrome and renal or pulmonary dysfunction. DF stabilizes activated ECs and protect them from further injury. Intravenous administration of DF before and after LPS injection significantly reduced mRNA expression of TNFα, IL6, Ang-2, E-, and P-selectin compared to controls. BALF showed decreased cellularity, reflecting less EC damage and leak. Allogeneic BMT mice were treated from day -1 through day 14 with DF intraperitoneally, and lungs were harvested at 3 weeks. Compared to controls, DF treatment reduced mRNA expression of TNFα, IL6, Ang-2, E-, and P- selectin, BALF cellularity, and lung histopathology. Conclusion: The administration of DF modulates EC injury in models of ARDS and IPS. Cytokine inhibition in combination with agents that stabilize EC integrity may be an attractive strategy for patients in each setting.